The Managerial Styles Of Malaysian Manager In The Public And Privatie Sectros - Mohamad Rajab, Abdul Wahab (Universiti Sains Malaysia, 1996)
This study cornparcs the managerial styles of Malaysian managers in the public and private sectors.It focuses on the five aspects of managerial styles; decision making, delegation, comn1unication, leadership and flexibility. · Of these five aspects, only leadership shows a significant difference. This coincides with the traditional belief that managers in the public sector are less participative than the private sector managers. It also indicates that the managerial styles of public sector managers are similar to the styles of private sector managers. This is partly due to government efforts in making the goverment agencies more user-friendly and customer focused. They tend to agree on the other four aspects. This is a good sign for Malaysian economy because the co.-operation between public and private sectors is needed in achieving Vision 2020.